Slurry for reflective coating and preparation method thereof
By using environmentally friendly and safe wetting agents, dispersants, coupling agents and binders in reflective coating materials, combined with titanium dioxide and glass microbeads, the problem of aging and deterioration of existing reflective coating materials in high temperature and ultraviolet environments is solved, and a high-performance and environmentally friendly reflective coating is achieved.
Patent Information
- Application Number
- CN202510392759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-10
AI Technical Summary
The existing reflective coating materials are prone to aging and deterioration in high temperature and high UV intensity environments, and the wetting agents, dispersants, coupling agents, binders, etc. used in the preparation process contain toxic polymers, affecting air quality.
SURFYNOL104E and citric acid solution were used as wetting agent and defoaming agent, bioresin extracted from the supra bark as dispersant, titanium dioxide and glass microbeads were suspended in the slurry, and sodium carboxymethylcellulose was added as the binder before coating to form a reflective coating with excellent performance.
It improves the hiding performance and weather resistance of the reflective coating, avoids environmental pollution, achieves the advantages of green and environmental protection, and has excellent reflective performance, meeting the application needs of road traffic safety facilities and other applications.
Smart Images

Figure CN120118566A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a reflective coating material, specifically to a slurry for a reflective coating and a preparation method thereof, which is a titanium dioxide slurry dedicated to a night reflective coating. Background Art
[0002] As an artificial composite material, reflective materials are widely used in various road traffic safety facilities such as traffic signs and markings, as well as vehicle license plates, clothing and shoes, fire protection, railways, water transportation, mining areas, etc. The crystal structure of titanium dioxide (TiO 2 ) gives it relatively high refractive index, covering power and whiteness, and has obvious advantages as a raw material for reflective coating materials, with stable reflective performance and strong weather resistance, which can extend the service life of the reflective coating.
[0003] Currently, the reflective coating materials are mainly based on glass microspheres and microprism structures. Such materials are prone to aging and deterioration when used in environments with high temperature and high ultraviolet intensity. Using titanium dioxide to replace part of the glass microspheres can improve problems such as the weather resistance of the coating. At present, although there are a small number of studies on using titanium dioxide as a reflective coating, the wetting agents, dispersants, coupling agents, binders, etc. used in the preparation process all incorporate a certain amount of toxic polymer, which seriously affects the air quality. Summary of the Invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a preparation method for a titanium dioxide slurry for a reflective coating. This method uses the solution of SURFYNOL104E and citric acid as a wetting agent and defoaming agent, uses the bio-resin extracted from lacquer tree bark as a dispersant. After uniform mixing, titanium dioxide and glass microspheres are suspended in a thick slurry, and adding sodium carboxymethyl cellulose as a binder before coating can form a reflective coating with excellent performance on the substrate; and because all reagents used in the slurry preparation process are non-toxic and pollution-free, it also has the advantages of being green and environmentally friendly, and is suitable for market promotion and application.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The first technical object of the present invention is to provide a preparation method for a slurry for a reflective coating, including the following steps:
[0007] 1) Select rutile titanium dioxide and an appropriate amount of glass microspheres, mix them into a uniform powder, add a small amount of SURFYNOL104E and citric acid solvent as a wetting agent, and adjust to a paste-like titanium dioxide slurry A for standby;
[0008] 2) crushing the Rhus verniciflua bark and adding an alcohol solution, extracting under reflux at 90-100° C. for about 2 hours, filtering after sufficient extraction, evaporating and condensing the obtained filtrate at ≤80° C. to recover the alcohol, eluting the remaining solution through a macroporous resin column, collecting the eluted part, and vacuum drying to a water content of 4-7wt%, thereby obtaining Rhus verniciflua bioresin;
[0009] 3) Weighing the Rhus verniciflua bioresin obtained in step 2), an alcohol solution (concentration 72-85%) and a titanate coupling agent in a mass ratio of 1:(6-10):(0.2-0.5), stirring and dissolving them to obtain a mixed solution M, slowly adding a titanium dioxide paste slurry A, stirring and volatilizing part of the alcohol at 70-80° C., and obtaining a slurry B;
[0010] 4) In another stirring container, distilled water and sodium carboxymethyl cellulose (CMC) are weighed in a mass ratio of (7-10):1, and stirred for 40-60 minutes under ultrasound assistance to obtain a binder solution N. The slurry B obtained in the above step 3) is slowly poured into the solution N while stirring. The mass ratio of slurry B to binder solution N is 1:(3.5-7). After fully stirring, the slurry for reflective coating is obtained.
[0011] It should be noted that, according to actual needs, the surface of the substrate to be coated is cleaned and leveled, and then the above-mentioned slurry is evenly coated and dried at a constant temperature of 60-80°C for 1-3 hours to obtain a reflective material with excellent reflective performance; and the number of times the slurry is applied can be determined according to the needs of different coating substrates and the service condition of the coating. The slurry has self-leveling properties, and different drying methods can be selected according to actual conditions.
[0012] Furthermore, the substrate is a surface such as cloth, plastic, metal, concrete, etc. to be coated. It needs to be cleaned and leveled before applying the reflective slurry to avoid peeling and falling off of the coating after the reflective coating is applied. After applying the reflective coating slurry, if actual conditions permit, dry it at a constant temperature of 60 to 80°C for 1 to 3 hours, and the coating will have a better bonding effect. When conditions are limited, use hot air to dry it to accelerate the bonding of the coating to the substrate surface. According to the use scenario of the reflective coating, adjust the slurry coating thickness. Under normal circumstances, the thickness of titanium dioxide used for reflective coating is 20 to 50 μm.
[0013] Optionally, the brightness of the rutile titanium dioxide selected in step 1) is ≥ 95%, and the TiO 2 The content is ≥95%, the oil absorption is ≤20g / 100g, the particle size is 0.2-0.5μm, the solid glass microbeads are 1-5μm in diameter and the density is 2.3g / cm 3, with a refractive index of 1.8 and a mixing mass ratio of titanium dioxide to glass beads of 3:2, titanium dioxide mixed powder is obtained; the SURFYNOL104E is used as a wetting agent, which is obtained by uniformly mixing 50% SURFYNOL104 (an alkynediol surfactant) and 50% ethylene glycol. Using SURFYNOL104E can reduce the surface tension of powder particles, eliminate the air bubbles on the powder surface and between particles, reduce agglomeration, so as to achieve the purpose of stabilizing the suspension. The specific preparation process of step 1) is as follows: Weigh SURFYNOL104 and ethylene glycol at a mass ratio of 1:1 respectively, place them in a stirring kettle at 40 - 50 °C and stir for about 1 h to fully dissolve, obtaining a SURFYNOL104E solution. Add citric acid at a ratio of 3 - 7% of the mass of the SURFYNOL104E solution, and continue to stir and dissolve. The resulting solution is a wetting agent and defoaming agent. Then add titanium dioxide mixed powder at 3 - 5 times the mass of this mixed solution, and continue to stir for 1 - 2 h to form a paste-like titanium dioxide slurry A, and the solid content of this slurry is about 80%.
[0014] Optionally, the lacquer tree bark in the above step 2) is a sun-dried product. After removing impurities, it is fully crushed, added with an alcohol solution (concentration 65 - 75%), placed in a water bath and reflux device for extraction and filtration for 2 h, and repeated 3 - 4 times. The alcohol recovered by evaporation and condensation can be recycled, and the resulting lacquer tree bio-resin is obtained.
[0015] Optionally, in the above step 3), first weigh the lacquer tree bio-resin obtained in step 2), alcohol solution (concentration 72 - 85%) and titanate coupling agent (the coupling agent used can improve the compatibility between titanium dioxide and organic solvents) at a mass ratio of 1:(6 - 10):(0.2 - 0.5) respectively, and fully stir and dissolve to obtain a mixed solution M (this solution is used as the main dispersant to prevent phenomena such as agglomeration, stratification and segregation after the slurry stands still). Then add the paste-like titanium dioxide slurry A obtained in step 1) at 3 to 6 times the mass of solution M, place it in a stirring kettle at 70 - 80 °C and stir to volatilize part of the alcohol, obtaining slurry B, and the solid content of the resulting slurry B is 65 - 80%.
[0016] Optionally, in the above step 4), add an appropriate amount of water to another container, then slowly add sodium carboxymethylcellulose (CMC, chemically pure, 300 - 800 mPa·s) in proportion, and fully stir for 40 - 60 min under ultrasonic assistance, and observe that there are no particles and agglomeration phenomena in the solution. The resulting mixed solution is the binder solution N. The slurry B needs to be slowly poured into the binder solution N, and at the same time, the stirring speed is slightly increased to avoid situations such as flocculation.
[0017] The second technical object of the present invention is to provide a slurry for a reflective coating prepared by the method as described above.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] 1. Currently, the reflective coating materials are mainly glass microspheres and microprism structures. Such materials are prone to aging and deterioration when used in environments with high temperatures and high ultraviolet intensities. High-end reflective coating composite materials still rely on imports, and there has always been environmental pollution caused by microplastics. The present invention uses a titanium dioxide coating to improve the covering performance and weather resistance of the coating.
[0020] 2. Some domestic and foreign studies have used titanium dioxide in reflective coatings such as road identification, safety warning, and reflective fabrics. However, most of them use ethers as wetting agents and other toxic organic substances as dispersants, coupling agents, and binders. The coatings prepared have a certain impact on air quality. The wetting agent, dispersant, coupling agent, binder, etc. used in the reflective coating prepared by the present invention are all environmentally friendly and safe reagents. There are no environmental pollution problems during both the coating preparation process and the coating material use process. It has the advantage of environmental friendliness, and the obtained reflective coating has excellent performance. Description of the Drawings
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only the embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained according to the provided drawings without creative efforts.
[0022] Figure 1 It is the laser particle size distribution diagram of the slurry prepared in Example 1 of the present invention. Among them, Curve 1 is the particle size distribution curve obtained by immediately sampling the prepared slurry (i.e., as obtained) and performing laser particle size testing, and Curve 2 is the particle size distribution curve obtained by sampling the prepared slurry after standing for 72 h and performing laser particle size testing.
[0023] Figure 2 Under the same conditions, the slurry is coated on a flat and smooth aluminum plate. After the coating is dried and stably adhered, the reflectivity is tested. The curve is the total specular / diffuse reflectivity. Detailed Embodiments
[0024] The following will clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.
[0025] As used herein, the term "embodiment" does not necessarily imply that any embodiment described as "exemplary" is superior or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application adopt conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific embodiments and are not intended to limit the content disclosed in this application.
[0026] Unless otherwise noted, the technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which this application belongs; other test methods and technical means not specifically noted in this application refer to the experimental methods and technical means commonly used by those of ordinary skill in the art.
[0027] To better illustrate the content of this application, numerous specific details are given in the following specific embodiments. Those skilled in the art should understand that this application can still be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well-known to those skilled in the art are not described in detail to highlight the gist of this application.
[0028] On the premise of no conflict, the technical features disclosed in the embodiments of this application can be combined arbitrarily, and the obtained technical solutions belong to the content disclosed in the embodiments of this application.
[0029] The present invention discloses a method for preparing a titanium dioxide slurry dedicated for a night reflective coating.
[0030] To better understand the present invention, the following embodiments are used to further specifically elaborate on the present invention, but it should not be construed as a limitation of the present invention. For those skilled in the art, some non-essential improvements and adjustments made according to the above-mentioned invention content are also considered to fall within the protection scope of the present invention.
[0031] Example 1
[0032] 1) Prepare the paste-like titanium dioxide slurry A
[0033] Weigh SURFYNOL104 (viscosity @ 55 °C (mpas) is 19, specific gravity is 0.89, Guangzhou Jieluhua Biotechnology Co., Ltd.) and ethylene glycol at a mass ratio of 1:1, place them in a stirring kettle at 50 °C and stir for 1 h to fully dissolve, obtaining the SURFYNOL104E solution. Weigh an appropriate amount of citric acid at a mass ratio of SURFYNOL104E solution: citric acid = 20:1, slowly add it to the SURFYNOL104E solution and stir fully to dissolve. The resulting solution is a wetting agent and defoaming agent. Mix titanium dioxide (titanium dioxide brightness ≥ 95%, TiO 2with a content of ≥95%, an oil absorption of ≤20 g / 100 g, and a particle size of 0.2 - 0.5 μm, where D50 is 0.3 μm) and glass microspheres (solid glass microspheres with a particle size of 1 - 5 μm and a density of 2.3 g / cm 3 , and a refractive index of 1.8) to obtain a titanium dioxide mixed powder; weigh the titanium dioxide mixed powder according to the ratio of the obtained solution to the mass of titanium dioxide of 1:4, and slowly add it to the obtained solution, and keep stirring until it becomes paste-like to obtain a paste-like titanium dioxide slurry A.
[0034] 2) Extract the biological resin of Rhus verniciflua
[0035] Select the dried Rhus verniciflua bark, remove impurities and crush it to a particle size of about 0.5 - 1 mm, add an alcohol solution with a concentration of 70%, transfer the obtained mixed solution to a water bath and reflux device, extract and filter it 4 times repeatedly, combine the obtained filtrates, evaporate and condense the filtrates at 80 °C, the condensed and recovered alcohol can be recycled, and the remaining solution is eluted through a macroporous resin column, and the eluted part is collected and vacuum dried to a water content of about 5 wt% to obtain the biological resin of Rhus verniciflua.
[0036] 3) Prepare a thick slurry B
[0037] Weigh appropriate amounts of the biological resin of Rhus verniciflua, alcohol with a concentration of 80%, and a titanate coupling agent (isopropyl tris(dioctylpyrophosphatooxy)titanate, Dongguan Kangjin New Materials Technology Co., Ltd.) according to the mass ratio of the biological resin of Rhus verniciflua: alcohol: titanate coupling agent = 5:40:1, and fully stir to obtain a mixed solution M. Weigh the paste-like titanium dioxide slurry A prepared in step 1) according to the mass ratio of solution M: slurry A = 1:4, slowly add it to the mixed solution M, stir while adding, transfer it to a stirring kettle and stir at 80 °C to volatilize part of the alcohol to obtain slurry B.
[0038] 4) Prepare a reflective coating slurry
[0039] Weigh appropriate amounts of sodium carboxymethyl cellulose (CMC, Sinopharm Chemical Reagent Co., Ltd.) according to the mass ratio of distilled water: sodium carboxymethyl cellulose = 8:1, slowly add it to the distilled water with stirring, fully stir for 50 min under ultrasonic assistance, and observe that there are no particles and agglomeration phenomena in the solution to obtain solution N. Weigh appropriate amounts of slurry B according to the mass ratio of slurry B: solution N = 1:5, slowly add it to solution N, and keep stirring until it is uniform to obtain the required reflective coating slurry.
[0040] 5) Coat the reflective coating
[0041] Select the rough fabric to be coated, clean it and dry it. Use a plastic brush to evenly coat the obtained reflective coating slurry on the fabric. Observe the leveling of the coating. After the slurry fills the small gaps in the fabric, coat it two more times until the surface of the coating is flat. Then transfer it to an incubator and dry it at 75°C for 1.5 h to obtain the reflective fabric.
[0042] The test results of the dispersion of the above-obtained slurry are as follows: the solid content is 72-75%, and the D10, D50, and D90 of the slurry before and after standing for 72 h differ by ≤10% each (it can be seen from the attached Figure 1 test results that curves 1 and 2 almost coincide, indicating that there are no phenomena such as agglomeration, stratification, and segregation in the slurry after standing for 72 h); the test results of the properties of the reflective fabric are as follows: the total / diffuse reflectance ≥95%, the adhesion is grade 1 (ISO2409), the weather resistance remains unchanged after 2300 h (UV lamp box UVB-313), and the retention rate of the retroreflective coefficient ≥86% (xenon lamp test), meeting the standard requirements of ≥80% for the retention rate of the retroreflective coefficient in JT / T1327-2020.
[0043] Example 2
[0044] Repeat Example 1, except that:
[0045] ① The substrate to be coated is the road surface. Prepare a wetting agent solution by mixing SURFYNOL104E solution and citric acid according to a mass ratio of 20:1. Weigh the titanium dioxide mixed powder according to the ratio of the obtained solution to titanium dioxide of 1:5, and stir to obtain a paste-like titanium dioxide slurry A; Weigh appropriate amounts of lacquer tree bioresin, 80% alcohol, and titanate coupling agent according to the mass ratio of lacquer tree bioresin: alcohol: titanate coupling agent = 5:35:1, and stir well to obtain a mixed solution M. Mix according to the mass ratio of solution M: slurry A = 1:5 to obtain slurry B. The heating temperature of the stirring kettle is 85°C. Due to the uncertainty of the road service conditions, it is necessary to appropriately increase the stable thickness of the coating, so the obtained slurry is thicker and has a higher solid content than that in Example 1;
[0046] ② Due to the uncertainty of the road service conditions, it is necessary to appropriately increase the adhesion between the coating and the substrate. Distilled water and sodium carboxymethylcellulose are prepared according to a ratio of 5:1, and the stirring time is extended to 1.5 h.
[0047] ③ Clean the dust on the road surface to be coated, apply the above N to the surface, and then coat the prepared reflective coating slurry 3-4 times. Due to the uncertainty of the road service conditions, the coating needs to solidify and dry faster. The slurry needs to be heated to 60°C before coating, and a hot air blower is used for rapid drying after brushing.
[0048] The test results of the dispersion of the obtained slurry are as follows: the solid content is 75-80%, and the differences in D10, D50, and D90 of the slurry before and after standing for 72 hours are all ≤ 10% (sampling by layering with a straw); the test results of the performance of the reflective fabric are as follows: the total / diffuse reflectance is ≥ 95%, the adhesion is grade 0 (ISO2409), and the weather resistance remains unchanged in color, without blistering or peeling after 3200 hours (UV lamp box UVB-313), meeting the requirements of the GB / T23987-2019 standard.
[0049] Example 3
[0050] Repeat Example 1, except that:
[0051] ① The substrate to be coated is the outer surface of an I-beam. A slurry with better fluidity is required. Weigh appropriate amounts of lacquer tree bioresin, alcohol with a concentration of 72%, and titanate coupling agent according to the mass ratio of lacquer tree bioresin: alcohol: titanate coupling agent = 5:50:1, and fully stir to obtain a mixed solution M. According to the mass ratio of solution M: slurry A = 1:3.5, mix to prepare slurry B, and the solid content of the obtained slurry is smaller than that in Example 1;
[0052] ② Since the surface of the I-beam is smoother than that of the fabric and the coating is not easily penetrated and adhered, it is necessary to appropriately increase the adhesion between the coating and the substrate. Distilled water and sodium carboxymethylcellulose are prepared according to the ratio of 5:1, and the stirring time is extended to 1.5 hours;
[0053] ③ Clean the oil stains, paint, rust, etc. on the surface of the I-beam to be coated, and then apply the prepared reflective coating slurry 3 times. After brushing, use a hot air blower to dry it quickly.
[0054] To verify the reflectivity of the reflective coating, under the same conditions, the slurry is coated on a flat and smooth aluminum plate. After the coating is dried and adhered stably, the reflectivity test is carried out (as shown in the appendix Figure 2 ). It can be seen from the test results that when the incident wavelength is about 500 nm, the total reflectivity reaches the peak value and exceeds 95%.
[0055] The test results of the dispersion of the obtained slurry are as follows: the solid content is 62-65%, and the differences in D10, D50, and D90 of the slurry before and after standing for 72 hours are all ≤ 10% (sampling by layering with a straw); the test results of the performance of the reflective fabric are as follows: the total / diffuse reflectance is ≥ 95%, the adhesion is grade 0 (ISO2409), the weather resistance remains unchanged in color, without blistering or peeling after 3200 hours (UV lamp box UVB-313), and the retention rate of the retroreflective coefficient ≥ 86% (xenon lamp test), meeting the standard requirement of the retention rate of the retroreflective coefficient ≥ 80% in JT / T1327-2020.
[0056] The foregoing description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a slurry for a reflective coating, comprising the following steps: 1) Prepare SURFYNOL104E solution, add citric acid, mix the resulting solution as a wetting agent, add a powder obtained by mixing rutile titanium dioxide and glass microspheres, and prepare a paste-like titanium dioxide slurry A; 2) extracting the Rhus verniciflua bioresin from the Rhus verniciflua bark with alcohol, then evaporating and condensing the alcohol, eluting the remaining solution through a macroporous resin column, and then drying the Rhus verniciflua bioresin to be used as a main dispersant for the slurry; 3) Weigh the Rhus verniciflua bioresin, alcohol solution and titanate coupling agent prepared in step 2) respectively, stir and dissolve them to obtain a mixed solution M, slowly add the titanium dioxide paste A prepared in step 1), stir and volatilize part of the alcohol at 70-80° C., and obtain slurry B; 4) Weigh sodium carboxymethyl cellulose (CMC) and dissolve it in distilled water. Stir it thoroughly under ultrasound assistance to obtain a binder solution N. Then slowly pour the slurry B prepared in step 3) into the binder solution N while stirring. After fully stirring, the slurry for reflective coating is obtained.
2. The method for preparing a slurry for a reflective coating according to claim 1, characterized in that: In step 1), citric acid is added to the SURFYNOL104E solution to prepare a wetting agent and defoaming agent for the slurry, and the amount of citric acid added is 3-7% of the mass of the SURFYNOL104E solution; according to different coating substrates and coating service conditions, different masses of titanium dioxide mixed powder are added to prepare paste slurry A with different solid contents.
3. The method for preparing the slurry for reflective coating according to claim 2, characterized in that: The rutile titanium dioxide has a brightness of ≥95%, a TiO2 content of ≥95%, an oil absorption of ≤20g / 100g, and a particle size of 0.2-0.5μm; the glass microspheres have a particle size of 1-5μm and a density of 2.3g / cm 3 , refractive index 1.8, the mixing mass ratio of titanium dioxide to glass microspheres is 3:2; the SURFYNOL104E is used as a wetting agent, and is obtained by uniformly mixing 50% SURFYNOL104 (acetylenic glycol surfactant) and 50% ethylene glycol.
4. The method for preparing a slurry for a reflective coating according to claim 1, characterized in that: In step 2), the Rhus verniciflua bark is dried, impurities are removed and then crushed to a particle size of 0.5-1 mm, and alcohol extraction, evaporation, condensation and macroporous resin elution are used to obtain Rhus verniciflua bioresin, which is then dried to a moisture content of 4-7 wt%.
5. The method for preparing a slurry for a reflective coating according to claim 1, characterized in that: In step 3), the mass ratio of the Rhus verniciflua bioresin, alcohol solution (concentration 72-85%) and titanate coupling agent is 1:(6-10):(0.2-0.5); the mass of the added slurry A is 3-6 times the mass of the mixed solution M, and the solid content of the slurry B is 65-80%.
6. The method for preparing a slurry for a reflective coating according to claim 1, characterized in that: In step 4), the prepared binder solution is prepared according to different coating substrate requirements and coating service conditions. The ratio of distilled water to sodium carboxymethyl cellulose (CMC) is different, and the viscosity and bonding force of the obtained binder solution are also different; the mass ratio of distilled water to sodium carboxymethyl cellulose (CMC) is (7-10):
1.
7. The method for preparing the slurry for reflective coating according to claim 6, characterized in that: The mass ratio of slurry B to binder solution N is 1:(3.5-7).
8. A slurry for reflective coating prepared by the method of claim 1.